Nature and Dimensions of Systemic Hyperinflammation and its Attenuation by Convalescent Plasma in Severe COVID-19. (12th January 2021) - Bandopadhyay, Purbita; D'Rozario, Ranit; Lahiri, Abhishake; Sarif, Jafar; Ray, Yogiraj; Paul, Shekhar Ranjan; Roy, Rammohan; Maiti, Rajshekhar; Chaudhuri, Kausik; Bagchi, Saugata; Maiti, Ayan; Perwez, Mohammed Masoom; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causing coronavirus disease 2019 (COVID-19), has led to significant morbidity and mortality. While most suffer from mild symptoms, some patients progress to severe disease with acute respiratory distress syndrome (ARDS) and associated systemic hyperinflammation. Methods: First, to characterize key cytokines and their dynamics in this hyperinflammatory condition, we assessed abundance and correlative expression of a panel of 48 cytokines in patients progressing to ARDS as compared to patients with mild disease. Then, in an ongoing randomized controlled trial of convalescent plasma therapy (CPT), we analyzed rapid effects of CPT on the systemic cytokine dynamics as a correlate for the level of hypoxia experienced by the patients. Results: We identified an anti-inflammatory role of CPT independent of its neutralizing antibody content. Conclusions: Neutralizing antibodies, as well as reductions in circulating interleukin-6 and interferon-γ–inducible protein 10, contributed to marked rapid reductions in hypoxia in response to CPT. Clinical Trial Registry of India: CTRI/2020/05/025209. http://www.ctri.nic.in/ Abstract : Characterization of hyperinflammation in COVID-19 revealed the dominant cytokines and identified MCP-3 as a correlate for clinical improvement. An anti-inflammatory role of convalescent plasma independent of neutralizing antibodies was revealed, which with neutralizing antibodies contributed to rapid reductions in hypoxia.